Evaluación de la aplicación de reglas y normas de bioseguridad, en la clínica y maternidad Heriberto García del cantón Buena Fe, en el primer trimestre 2013 - Franco Coello, Norta Mercedes (2013)
Talking Biosecurity is reference to life, necessary to protect the existence of human beings and their health care security measures exist for this and / or preventive barriers, and they are the basic safety rules that we help preserve the health and life. The present work aims to make rules and implement biosafety regulations, Heriberto Garcia Clinic in Canton Buena Fe in the province of Rivers, with the aim of providing quality service without biological risks It is important to the application of rules and standards of biosecurity, as in health units there is no proper marking of containers for waste, also the maintenance program is highly flawed, and that cleaning practice one day, and is common to find significant amounts of debris on the floor, second shows that the waste is not classified and all are placed in a single container Establishing Standards Biosafety main objective is the reduction of occupational hazards in every leve , so that should be followed thoroughly. The result of this research is to verify compliance with rules and regulations apply biosecurity q Clinic Heriberto Garcia, the Canton Good Faith.